OP13 Mucosal organoids capture Innate Lymphoid Cells (ILC) tissue-specific development and reveal that Inflammatory Bowel Disease-associated ILC modulate intestinal remodelling. (27th May 2021) - Jowett, G M; Read, E; Norman, M D; Arevalo, P A; Vilà González, M; Roberts, L; Vallier, L; Curtis, M; Lord, G; Gentleman, E; Neves, J F
Abstract: Background: Innate Lymphoid Cells (ILC) develop from Common Lymphoid Precursors in the bone marrow, and ILC precursors (ILCP) migrate to mucosa where they mature, promote homeostasis, and provide a potent, antigen-non-specific sources of cytokines. Deciphering what local stimuli drive the final stages of ILCP maturation in these tissues remains a pressing question, as ILC frequencies can become dysregulated during chronic infection and inflammatory diseases. For example, Type-1 innate lymphoid cells (ILC1) are enriched in the mucosa of patients with active inflammatory bowel disease (IBD) and the impact of this accumulation remains elusive. Methods: Here, we develop and use co-cultures of both murine and human iPSC-derived gut and lung organoids with ILCP and with mature ILC isolated from IBD patients' intestinal biopsies. Results: Harnessing these versatile models, we demonstrate that epithelial cells provide a complex niche capable of supporting the final maturation of all helper-like ILC1, ILC2, and ILC3. Notably, organoid identity was sufficient to robustly recapitulate tissue-specific ILC imprints and frequencies, even in the absence of microbial stimuli, other cell types, or cytokine supplementation. In addition, we show that that ILC1 drive expansion of the epithelial stem cell crypt through p38γ phosphorylation, driving a potentially pathological proliferative feedback loop between β-catenin and Cd 44 v6. We harnessed this model to elucidate that this phenotype was unexpectedly regulated by ILC1-derived TGFβ1. We further show that human gut ILC1 also secrete TGFβ1, and drive CD 44 v6 expression in both HIO epithelium and mesenchyme. As TGFβ1 is a master regulator of fibrosis, the leading indicator for surgery in IBD, we next characterised the ability of ILC1 to regulate matrix remodelling using a functionalized, synthetic hydrogel system. We show that ILC1 drive both matrix stiffening and degradation, which we posit occurs through a balance of MMP9 degradation and TGFβ1-induced fibronectin deposition. Conclusion: Taken together, our work provides unprecedented insight into in situ ILC maturation, which we show to be driven by epithelial signals, and into ILC function. We also report that intestinal ILC1 modulate epithelial and matrix remodelling, which may drive either wound healing in homeostasis, but may tip toward pathology when enriched in IBD. Moreover, our work introduces a modular organoid platform, which provides exquisite control over both environmental stimuli and host genetics, making it a powerful tool for dissecting the interactions between complex mucosal tissues and rare cell subtypes in development and disease.